Female Genital Cosmetic Surgery Deviance, Desire and the Pursuit of Perfection - Nurka, Camille; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
Examining the fascinating history of female genital cosmetic surgery, Camille Nurka traces the origins of contemporary ideas of genital normality. Over the past twenty years, Western women have become increasingly worried about the aesthetic appearance of their labia minora and are turning to cosmetic surgery to achieve the ideal vulva: a clean slit with no visible protrusion of the inner lips. Long labia minora are described by medical experts as 'hypertrophied,' a term that implies deformity and the atypical. But how far back does the diagnosis of labial hypertrophy go, and where did it originate? Female Genital Cosmetic Surgery tells the story of the female genitalia from the alien world of ancient Greek gynaecology to the colonial period of exploration and exploitation up to the present day. Bringing together historical, medical, and theoretical documentation and commentary, Nurka uncovers a long tradition of pathologizing female anatomy, a history sure to beof interest to any reader who wishes to know more about how medicine shapes our commonly held ideals. .
1. Introduction -- 2. Ancient Anatomies -- 3. Galen's Nymphs -- 4. The Colonial Races Sciences -- 5. Sexual Anthropometry -- 6. Deviant Desires -- 7. Desiring Normality -- 8. DIY Sex.
Keywords: Sex; Human body -- Social aspects; Social medicine; Sociology; Gender Studies; Sociology of the Body; Medical Sociology; Sociological Theory